The Effect of Ownership Structure and Leverage Towards Dividend Policy and Corporate Values - Endang, MG Wi; Suhadak, Suhadak; Saifi, Mohammad; Firdausi, Nila (JPAS (Journal of Public Administration Studies), 2020)
Every company (particularly the company's shareholders) always expects to have high company value. Various mechanisms are used by company managers to create corporate value. The mechanism can be through the structure of ownership, leverage, and dividend policy. Previous studies that have discussed the effect of ownership structure and leverage variables on dividend policy and corporate value provide different research results. This study aims to obtain empirical evidence of the effect of ownership structure and leverage on dividend policy and firm value, on manufacturing companies listed on the Indonesia Stock Exchange in the 2012-2016 period. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange that provide periodic financial statements from 2012 to 2016 (145 companies). The population that met the criteria to sampled was 28 companies. The research method used in this research is Warp-PLS. The results showed as follows: (1) The effect of ownership structure on dividend policy was negative and not significant; (2) The effect of ownership structure on firm value was negative and significant; (3) The leverage on dividend policy was negative and significant; (4) The leverage on the company value was negative and weak significant correlation; (5) The effect of the dividend policy on corporate value was negative and weak significant correlation.